The Application of 2-Naphthols in Asymmetric Synthesis of Atropisomers - Xiang, Shao-Hua; Cheng, Jun Kee; Tan, Bin (Synlett, 2022)
The venerable axially chiral biaryl skeletons used widely in asymmetric catalysis such as BINOLs, NOBINs, QUINOLs, and CPAs possess a 2-naphthol moiety or are derived from the naphthol precursor. The hydroxy functionality offers the interaction point or serves as functional handle for synthetic elaboration. This prevalence and significance drive our studies to incorporate this nucleophile class to fabricate an assortment of atropisomers. By activating the reacting partners via distinctive mechanisms, the arylation of quinones, azo- or nitroso-naphthalenes, VQM intermediates, 1,2,4-triazole-3,5-diones, isoquinolines, and 1-bromo-2-naphthols with 2-naphthols were successfully attained. A concise account of these developments is provided in this article.1 Introduction2 Asymmetric Arylation with Quinones3 Asymmetric Arylation with Electron-Deficient Arenes4 Asymmetric Synthesis of Atropisomers with other Electrophiles5 Conclusion
Keywords: atropisomers; 2-naphthols; asymmetric synthesis; organocatalysis; arylation; quinones; election-deficient arenes